Mobile Physiological Measurement Platform With Cloud and Analysis Functions Implemented via IPSO - Sung, Wen-Tsai; Chen, Jui-Ho; Chang, Kung-Wei (IEEE sensors journal, 2014)
A physiological measurement platform is proposed for enabling users to measure physical condition regularly and to maintain good physical condition. The proposed system combines three basic physiological signal acquisition modules: an ECG module, a blood pressure module, and an oxygen saturation module. The physiological signals captured by the three physiological signal acquisition modules are sent via a data interface module to a mobile handheld device. Three communication systems are used for data transmission: RS-232 serial port wired transmission wireless, ZigBee, and Bluetooth. The captured physiological signals are presented on Android system mobile handheld devices, and the physiological data received by the mobile handheld device are sent to the cloud server via the Internet. After establishing a personal physiological database in the cloud server, the improved particle swarm optimization algorithm is used to determine the best personal physiological data, while setting physiological data dangerous levels for preliminary diagnosis. The dangerous levels are adjusted and set according to the personal medical records and physiological data of the subjects. When the physiological data reach the designated danger levels, it gives a warning to seek timely treatment by a medical unit. Finally, the system can incorporate video equipment to enable remote diagnosis and consultation by medical units.